A ZrCu-MOG material for cascade degradation of organophosphorus nerve agents and its preparation method and application

By synthesizing ZrCu-MOG material and utilizing its bimetallic active sites, the cascade degradation of methyl paraoxon is achieved, which solves the problems of unstable natural enzymes and complicated preparation processes in the existing technology, and achieves high efficiency and low cost. Degradation effect of organophosphorus nerve agents.

CN118681601BActive Publication Date: 2025-01-24CHONGQING NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410721169.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-01-24
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

When the prior art degrades organophosphorus nerve agents in cascade, there are problems such as instability of natural enzymes, complex preparation process and high cost, making it difficult to achieve large-scale production and practical application.

Method used

Design and synthesize the ZRCU-MOG material, by mixing the hybrid solution containing ZR4+and CU2+with 2,4,6-three [((to the carboxyl phenyl) ammonia group] -1,3,5-triazine solution mix at room temperature and prepare for preparation Materials with dual metal active sites simplify the preparation process and reduce costs.

Benefits of technology

Achieved the oxygen -phosphorus degradation of methyl -based oxygen phosphorus. Firstly, it degrades it into a nitrate phenol, and then further degrades into non -toxic amino phenol to solve the toxic problem of secondary hydrolyzed products. , Suitable for large -scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118681601B_ABST
    Figure CN118681601B_ABST
Patent Text Reader

Abstract

The present invention provides a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents and a preparation method and application thereof, belonging to the technical field of nanomaterials. The ZrCu-MOG material for cascade degradation of organophosphorus nerve agents is a ZrCu-MOG material containing Zr 4+ and Cu 2+ The mixed solution is mixed with 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution at room temperature, allowed to stand, washed and dried to obtain a Zr 4+ , Cu 2+ The ions are loaded in the network structure of MOG, thus constructing a ZrCu-MOG material with bimetallic active sites. The bimetallic ZrCu-MOG material has dual active sites, which can not only achieve the degradation of DMNP, but also further reduce the secondary product p-NP of DMNP to p-AP, which is non-toxic and has certain economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents and a preparation method and application thereof. Background Art

[0002] As a chemical warfare agent, organophosphorus nerve agents are highly toxic and cause great harm to the human body. Organophosphorus nerve agents can covalently bind acetylcholinesterase to the active site, irreversibly inhibit the normal function of the enzyme, directly interfere with the operation of the central nervous system, and in severe cases can cause suffocation or even death. At present, a variety of functional materials have been developed for the degradation of organophosphorus nerve agents, including cerium oxide nanoparticles, metal organic frameworks (MOFs) and their derivatives. Although these materials have achieved efficient degradation of organophosphorus, their hydrolysis products are still highly toxic and still pose a potential threat to the environment and human health. For example, the hydrolysis products of general organophosphorus nerve agents, such as parathion and paraoxon, contain p-nitrophenol (p-NP). p-NP is one of the more difficult pollutants to treat and has great harm to the nervous system, blood cells, liver and kidneys. The reduction product of p-NP, p-aminophenol (p-AP), is not only almost non-toxic to the human body and the environment, but also an important intermediate for the preparation of cosmetics and antipyretic and analgesic drugs. Therefore, further degradation of the secondary hydrolysis products of organophosphorus nerve agents into non-toxic and economically beneficial compounds would be a potentially effective strategy to address this unique challenge.

[0003] At present, methods for cascade degradation of organophosphorus nerve agents have been proposed in the relevant field, most of which are through the combination of natural enzymes and nanomaterials. However, due to the instability of natural enzymes, difficulty in storage, and the complex preparation process of composite catalysts, their application is limited. The patent application number 202010391650.9 is related to "the preparation method of organophosphorus degradation enzyme-based multifunctional catalyst and organophosphorus degradation enzyme-based multifunctional catalyst and its application", which proposes a preparation method of organophosphorus degradation enzyme-based multifunctional catalyst. The advantage is that the multifunctional catalyst overcomes the problems of poor stability of organophosphorus degradation by existing organophosphorus hydrolases and incomplete degradation products. However, this method has some defects and shortcomings, including: (1) This method uses biological enzymes to degrade organophosphorus, and its stability is easily affected by the external environment, and the degradation conditions are strictly required; (2) The preparation process of the multifunctional catalyst involves bacterial transcription and expression of organophosphorus degradation enzymes, preparation of composite yolk-shell structure nanomaterials, and loading of organophosphorus degradation enzymes. The overall process is complex and has high technical requirements, which is not suitable for promotion and use. In addition, the patent with application number 202110127343.4 discloses a method of "using COFs to fix palladium and organophosphorus hydrolase to construct hybrid catalysts and cascade degradation of organophosphorus nerve agents". This method fixes ultrafine palladium metal nanoparticles and biological enzymes to covalent organic frameworks, thereby providing a new strategy for the preparation of hybrid catalysts, and at the same time uses the bifunctional hybrid catalyst to achieve cascade degradation of organophosphorus nerve agents. However, this method also has some defects and shortcomings, including: (1) The functional catalyst combines natural enzymes with COFs materials, and there is still the problem of poor stability caused by the intolerance of natural enzymes to environmental conditions; (2) The functional catalyst also has the problem of complex synthesis process, long cycle, and high cost caused by the use of precious metals.

[0004] Therefore, designing and synthesizing a cascade degradation catalyst for organophosphorus nerve agents that has a simple, rapid, low-cost preparation process and is suitable for large-scale production can greatly promote its practical application development. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides a method for preparing a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents, comprising: 4+ and Cu 2+ The mixed solution is mixed with 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine (H3TATAB) solution at room temperature, left to stand, washed and dried to obtain the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents.

[0007] Furthermore, the concentration of the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 0.138 mol / L.

[0008] Furthermore, the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is obtained by dissolving 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine in water containing triethylamine (TEA).

[0009] Furthermore, the Zr-containing 4+ and Cu 2+ The volume ratio of the mixed solution to the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 1:1.

[0010] Furthermore, the Zr-containing 4+ and Cu 2+ The mixed solution consists of Zr with a concentration of 0.069 mol / L 4+ solution and Cu with a concentration of 0.069 mol / L 2+ The solution is prepared.

[0011] Furthermore, the Zr 4+ Solution and Cu 2+ The volume ratio of the solution is 333:21.

[0012] Furthermore, the Zr-containing 4+ and Cu 2+ The mixed solution includes Zr in a volume ratio of 333:21:146 4+ Solution, Cu 2+ solution and water.

[0013] The present invention also provides a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents prepared by the preparation method.

[0014] The present invention also proposes the use of the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents in cascade degradation of organophosphorus nerve agents, wherein the organophosphorus nerve agent is methyl paraoxon (DMNP), and the ZrCu-MOG material cascade degrades methyl paraoxon (DMNP) into p-aminophenol (p-AP).

[0015] Further, the following steps are included:

[0016] The ZrCu-MOG material for cascade degradation of organophosphorus nerve agents is dissolved in water to obtain a ZrCu-MOG material aqueous solution, and mixed with a methyl paraoxon (DMNP) solution and an N-ethylmorpholine (N-EM) buffer solution at room temperature for reaction for 30 minutes, thereby degrading the methyl paraoxon (DMNP) into p-nitrophenol (p-NP);

[0017] Then, NaBH4 solution was added to the mixed solution after the above reaction (containing p-nitrophenol (p-NP)), and the mixture was mixed and reacted at room temperature for 20 minutes, thereby degrading p-nitrophenol (p-NP) into p-aminophenol (p-AP), thereby achieving the cascade degradation of methyl paraoxon (DMNP).

[0018] Furthermore, the concentration of the ZrCu-MOG material aqueous solution is 0.82 mg / mL, and the concentration of the NaBH4 solution is 0.5M.

[0019] Furthermore, the concentration of the N-ethylmorpholine (N-EM) buffer solution is 0.45 M and the pH is 10.

[0020] Furthermore, the volume ratio of the ZrCu-MOG material aqueous solution to the methyl paraoxon solution and the NaBH4 solution is 3:2:4.

[0021] Compared with the prior art, the present invention has the following advantages and technical effects:

[0022] (1) The present invention utilizes the coordination effect between metal ions and organic ligands, and Zr 4+ , Cu 2+ Ions are loaded in the network structure of MOG (hydrogel), thereby constructing a ZrCu-MOG material with a bimetallic active site, simplifying the material preparation process; and no natural enzymes and precious metals are needed, greatly reducing the preparation cost; and also avoiding the problem of incompatibility of nanomaterials with different functions in the synthesis process of composite nanocatalysts. The bimetallic ZrCu-MOG material obtained by the present invention has a dual active site, and the Zr(IV) node in the ZrCu-MOG material can efficiently degrade the organophosphorus nerve agent methyl paraoxon (DMNP), while the Cu(II) node can further reduce the secondary toxic product p-nitrophenol (p-NP) to p-aminophenol (p-AP) which is non-toxic and has certain economic benefits. Therefore, the ZrCu-MOG material of the present invention can not only achieve the degradation of DMNP, but also further reduce the secondary product p-NP of DMNP to p-AP which is non-toxic and has certain economic benefits.

[0023] (2) In the present invention, Zr 4+ , Cu 2+The ZrCu-MOG material with a large specific surface area, a porous structure and abundant active sites can be obtained by mixing the metal ion mixed solution with the ligand solution at room temperature. The synthesis method is rapid, mild and easy to operate, and is suitable for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0025] Figure 1 This is a schematic diagram of the preparation process of a Zr / Cu-MOG material for cascade degradation of organophosphorus nerve agents in Example 1;

[0026] Figure 2 The SEM measurement results of the ZrCu-MOG material prepared in Example 1;

[0027] Figure 3 TEM measurement results of ZrCu-MOG material prepared in Example 1;

[0028] Figure 4 This is the BET test result of the ZrCu-MOG material prepared in Example 1;

[0029] Figure 5 The XRD test results of the ZrCu-MOG material prepared in Example 1;

[0030] Figure 6 The XPS test results of the ZrCu-MOG material prepared in Example 1;

[0031] Figure 7 The results of measuring the conversion rate of DMNP in the reaction system at different DMNP degradation times in step 1 of Example 2;

[0032] Figure 8 The p-NP conversion rate in the reaction system at different degradation times in step 2 of Example 2 is measured;

[0033] Fig. 9 The ZrCu-MOG material obtained in Example 1 was subjected to 5 cycles of degradation reaction, and the relative activity was measured after each reaction;

[0034] Fig.10 The results of measuring the conversion rate of DMNP in the reaction system at different DMNP degradation times in step 1 of comparative example 3 are as follows;

[0035] Fig.11 The results of measuring the p-NP conversion rate in the reaction system at different degradation times in step 2 of comparative example 3;

[0036] Fig.12 The results of measuring the conversion rate of DMNP in the reaction system at different DMNP degradation times in step 1 of comparative example 5 are as follows;

[0037] Fig.13 These are the results of measuring the DMNP conversion rate in the reaction system at different DMNP degradation times in step 1 of comparative example 7. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0043] The embodiment of the present invention provides a method for preparing a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents, comprising: 4+ and Cu 2+The mixed solution is mixed with 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine (H3TATAB) solution at room temperature, left to stand, washed and dried to obtain the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents.

[0044] In a preferred embodiment of the present invention, the concentration of the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 0.138 mol / L.

[0045] In a preferred embodiment of the present invention, the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is obtained by dissolving 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine in water containing triethylamine (TEA).

[0046] In a preferred embodiment of the present invention, the Zr-containing 4+ and Cu 2+ The volume ratio of the mixed solution to the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 1:1.

[0047] In a preferred embodiment of the present invention, the Zr-containing 4+ and Cu 2+ The mixed solution consists of Zr with a concentration of 0.069 mol / L 4+ solution and Cu with a concentration of 0.069 mol / L 2+ The solution is prepared.

[0048] In a preferred embodiment of the present invention, the Zr 4+ Solution and Cu 2+ The volume ratio of the solution is 333:21.

[0049] In a preferred embodiment of the present invention, the Zr-containing 4+ and Cu 2+ The mixed solution includes Zr in a volume ratio of 333:21:146 4+ Solution, Cu 2+ solution and water.

[0050] In a preferred embodiment of the present invention, the Zr 4+ The solution is a ZrCl4 solution, the Cu 2+ The solution is CuSO4·5H2O solution.

[0051] The embodiment of the present invention also provides a ZrCu-MOG material prepared by the preparation method for cascade degradation of organophosphorus nerve agents.

[0052] The embodiment of the present invention also proposes the use of the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents in cascade degradation of organophosphorus nerve agents, wherein the organophosphorus nerve agent is methyl paraoxon (DMNP), and the ZrCu-MOG material cascade degrades methyl paraoxon (DMNP) into p-aminophenol (p-AP), specifically comprising the following steps:

[0053] The ZrCu-MOG material for cascade degradation of organophosphorus nerve agents is dissolved in water to obtain a ZrCu-MOG material aqueous solution, and mixed with a methyl paraoxon (DMNP) solution and an N-ethylmorpholine (N-EM) buffer solution at room temperature for reaction for 30 minutes, thereby degrading the methyl paraoxon (DMNP) into p-nitrophenol (p-NP);

[0054] Then, NaBH4 solution was added to the mixed solution after the above reaction (containing p-nitrophenol (p-NP)), and the mixture was mixed and reacted at room temperature for 20 minutes, thereby degrading p-nitrophenol (p-NP) into p-aminophenol (p-AP), thereby achieving the cascade degradation of methyl paraoxon (DMNP).

[0055] In a preferred embodiment of the present invention, the concentration of the aqueous solution of the ZrCu-MOG material is 0.82 mg / mL, the concentration of the methyl paraoxon solution is 2 mM (however, the ZrCu-MOG material of the present invention is not only suitable for the cascade degradation of methyl paraoxon at a concentration of 2 mM, but can also be used for the degradation of methyl paraoxon at higher or lower concentrations), and the concentration of the NaBH4 solution is 0.5 M.

[0056] In a preferred embodiment of the present invention, the concentration of the N-ethylmorpholine (N-EM) buffer solution is 0.45 M and the pH is 10.

[0057] In a preferred embodiment of the present invention, the volume ratio of the ZrCu-MOG material aqueous solution to the methyl paraoxon solution and the NaBH4 solution is 3:2:4.

[0058] The room temperature in the embodiments of the present invention refers to "25±3°C".

[0059] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0060] The technical solution of the present invention is further illustrated by the following embodiments.

[0061] Example 1

[0062] A schematic diagram of the preparation process of Zr / Cu-MOG material for cascade degradation of organophosphorus nerve agents is shown in Figure 1 , specifically including the following steps:

[0063] (1) ZrCl4 (160.8 mg, 0.69 mmol) and CuSO4·5H2O (172.3 mg, 0.69 mmol) were dissolved in 10 mL of ultrapure water and ultrasonicated to fully dissolve them to obtain ZrCl4 solution and CuSO4·5H2O solution with a concentration of 0.069 mol / L;

[0064] (2) 167.8 mg (0.69 mmol) of H3TATAB was added to 4 mL of ultrapure water, and 200 μL of TEA was added to promote its dissolution in water, followed by sonication to fully dissolve it. Finally, the solution was diluted to 5 mL to obtain a H3TATAB solution with a concentration of 0.138 mol / L;

[0065] (3) 333 μL of the ZrCl4 solution obtained in step (1) was mixed with 21 μL of CuSO4·5H2O solution and 146 μL of H2O to obtain 500 μL of a mixed solution, and then 500 μL of the H3TATAB solution obtained in step (2) was quickly added to the mixed solution and vortexed for 2 seconds. After standing at room temperature for 15 minutes, water-containing ZrCu-MOG was obtained;

[0066] (4) The aqueous ZrCu-MOG obtained in step (3) is centrifuged and washed three times with DMF and ultrapure water, and freeze-dried to obtain a dry ZrCu-MOG material for subsequent characterization and cascade degradation of organophosphorus nerve agents.

[0067] The SEM and TEM characterization results of the ZrCu-MOG material prepared in Example 1 are shown in Figure 2 and Figure 3 , it can be seen that the ZrCu-MOG material presents a fiber network structure, confirming that the material has a porous structure.

[0068] The ZrCu-MOG material prepared in Example 1 was subjected to BET test, and the results are shown in Figure 4 , it can be seen that the S BET =69.42m 2 / g, and the average pore size is 8.05nm, which further confirms the porosity of the material.

[0069] The ZrCu-MOG material prepared in Example 1 was subjected to XRD test, and the results are shown in Figure 5 , it can be seen that the prepared ZrCu-MOG material has an amorphous structure.

[0070] In order to further prove the successful synthesis of the material, the ZrCu-MOG material prepared in Example 1 was subjected to XPS test. Figure 6, it can be seen that the prepared ZrCu-MOG material contains C, O, N, Zr and Cu elements at the same time.

[0071] Example 2

[0072] Cascade degradation of DMNP by ZrCu-MOG materials

[0073] 1. Degradation of DMNP into p-NP

[0074] (1) The ZrCu-MOG material obtained in Example 1 was dispersed in ultrapure water to obtain a ZrCu-MOG material aqueous solution with a concentration of 0.82 mg / mL;

[0075] (2) taking 200 μL of DMNP ethanol solution (concentration of 2 mM) and adding it to a mixed solution containing 1000 μL of N-EM buffer solution, 300 μL of the ZrCu-MOG material aqueous solution obtained in step (1) and 500 μL of H2O, mixing and reacting at room temperature for different time periods (1-150 min) to obtain reaction mixed solutions at different reaction times, and centrifuging the mixed solution (12000 rpm, 1 min) to collect the supernatant;

[0076] (3) The absorbance of the supernatant in the range of 300-500 nm was measured by UV-visible spectrophotometer, where the absorption peak at 402 nm originated from the absorption of p-NP. The results of the determination of the conversion rate of DMNP in the reaction system at different DMNP degradation times are shown in Figure 7 ,It can be seen that the half-life of DMNP degradation by ZrCu-MOG material is about 30min, and DMNP can be degraded into p-NP within the half-life.

[0077] 2. Degradation of p-NP into p-AP

[0078] (1) 1000 μL of the reaction mixture solution obtained by reacting for 150 min in step 1 was taken from each of the five groups, and 800 μL of H2O and 400 μL of NaBH4 solution (0.5 M) were added to the supernatant to obtain a mixture;

[0079] (2) reacting the mixture obtained in step (1) at room temperature for different time periods (1-20 min), and finally, collecting the supernatant by centrifugation;

[0080] (3) The absorbance of the supernatant was measured by UV-visible spectrophotometer to determine the reduction and degradation of p-NP. The results of the p-NP content determination in the reaction system at different times are shown in Figure 8 , it can be seen that within 20 min, ZrCu-MOG material can completely convert p-NP into p-AP, thereby achieving complete degradation of DMNP.

[0081] Example 3

[0082] The mixed solution after the reaction in step 2 of Example 2 was centrifuged (12000rpm, 1min), the supernatant was removed, the ZrCu-MOG material at the bottom was retained, 1mL of ultrapure water was added for ultrasonic washing, and the mixture was centrifuged again (12000rpm, 1min) to obtain the recovered ZrCu-MOG material. The cascade degradation process of Example 2 was repeated 5 times with the recovered ZrCu-MOG material, and the amount of p-NP after each reaction was measured to evaluate the degradation performance of the ZrCu-MOG material. The relative activity results are shown in Fig. 9 (0 represents the end of degradation in Example 2, and 1-5 represent the number of repetitions in Example 3). It can be seen that after repeated use for 5 times, the activity of the ZrCu-MOG material can still retain about 80% of the initial activity, indicating that the ZrCu-MOG material has good catalytic degradation stability.

[0083] Comparative Example 1

[0084] (1) ZrCl4 (160.8 mg, 0.69 mmol) and CuSO4·5H2O (172.3 mg, 0.69 mmol) were dissolved in 10 mL of ultrapure water and ultrasonicated to fully dissolve them to obtain ZrCl4 solution and CuSO4·5H2O solution with a concentration of 0.069 mol / L;

[0085] (2) 111.8 mg (0.46 mmol) of H3TATAB was added to 4 mL of ultrapure water, and 200 μL of TEA was added to promote its dissolution in water. Ultrasonication was then performed to fully dissolve it, and the solution was finally diluted to 5 mL to obtain a H3TATAB solution with a concentration of 0.092 mol / L.

[0086] (3) 333 μL ZrCl4 solution obtained in step (1) was mixed with 21 μL CuSO4·5H2O solution and 146 μL H2O to obtain 500 μL mixed solution, and then 500 μL H3TATAB solution obtained in step (2) was quickly added to the mixed solution and vortexed for 2 seconds. After standing at room temperature for 15 minutes, no gel was formed. The main reason is that the concentration of H3TATAB is reduced, and the sites that can be combined with Zr and Cu metal ions are reduced, so ZrCu-MOG material cannot be synthesized.

[0087] Comparative Example 2

[0088] (1) ZrCl4 (160.8 mg, 0.69 mmol) was dissolved in 10 mL of ultrapure water and fully dissolved by sonication to obtain a ZrCl4 solution with a concentration of 0.069 mol / L;

[0089] (2) 167.8 mg (0.69 mmol) of H3TATAB was added to 4 mL of ultrapure water, and 200 μL of TEA was added to promote its dissolution in water, followed by sonication to fully dissolve it. Finally, the solution was diluted to 5 mL to obtain a H3TATAB solution with a concentration of 0.138 mol / L;

[0090] (3) Take 500 μL of the ZrCl4 solution obtained in step (1), then quickly add 500 μL of the H3TATAB solution obtained in step (2) to the above solution, vortex mix for 2 seconds, and stand at room temperature for 15 minutes to obtain water-containing Zr-MOG;

[0091] (4) The Zr-MOG obtained in step (3) is centrifuged and washed three times with DMF and ultrapure water, and freeze-dried to obtain a dry Zr-MOG material.

[0092] Comparative Example 3

[0093] Degradation of DMNP by Zr-MOG

[0094] 1. Degradation of DMNP into p-NP

[0095] (1) The Zr-MOG material obtained in Comparative Example 2 was dispersed in ultrapure water to obtain a Zr-MOG material aqueous solution with a concentration of 0.82 mg / mL;

[0096] (2) taking 200 μL of DMNP ethanol solution (concentration of 2 mM) and adding it to a mixed solution containing 1000 μL of N-EM buffer solution, 300 μL of the Zr-MOG material aqueous solution obtained in step (1) and 500 μL of H2O, mixing and reacting at room temperature for different time periods (1-150 min) to obtain reaction mixed solutions at different reaction times, and centrifuging all the above mixed solutions (12000 rpm, 1 min) to collect the supernatant;

[0097] (3) The absorbance of the supernatant in the range of 300-500 nm was measured by UV-visible spectrophotometer, where the absorption peak at 402 nm originated from the absorption of p-NP. The results of the determination of the conversion rate of DMNP in the reaction system at different DMNP degradation times are shown in Fig.10 It can be seen that the half-life of DMNP degradation by Zr-MOG material is also about 30 min, and DMNP can be degraded into p-NP within the half-life.

[0098] 2. Degradation of p-NP into p-AP

[0099] (1) 1000 μL of the reaction mixture solution obtained by reacting for 150 min in step 1 was taken from each of the five groups, and 800 μL of H2O and 400 μL of NaBH4 solution (0.5 M) were added to the supernatant to obtain a mixture;

[0100] (2) reacting the mixture obtained in step (1) at room temperature for different time periods (1-20 min), and finally, collecting the supernatant by centrifugation;

[0101] (3) The absorbance of the supernatant was measured by UV-visible spectrophotometer to determine the reduction and degradation of p-NP. The results of the p-NP content determination in the reaction system at different times are shown in Fig.11 , it can be seen that the Zr-MOG material without Cu active sites cannot convert p-NP into p-AP, and cannot achieve complete degradation of DMNP into p-AP.

[0102] Comparative Example 4

[0103] (1) CuSO4·5H2O (172.3 mg, 0.69 mmol) was dissolved in 10 mL of ultrapure water and sonicated to fully dissolve the solution to obtain a CuSO4·5H2O solution with a concentration of 0.069 mol / L;

[0104] (2) 167.8 mg (0.69 mmol) of H3TATAB was added to 4 mL of ultrapure water, and 200 μL of TEA was added to promote its dissolution in water, followed by sonication to fully dissolve it. Finally, the solution was diluted to 5 mL to obtain a H3TATAB solution with a concentration of 0.138 mol / L;

[0105] (3) taking 500 μL of the CuSO4·5H2O solution obtained in step (1), and then quickly adding 500 μL of the H3TATAB solution obtained in step (2) to the above solution, vortex mixing for 2 seconds, and standing at room temperature for 15 minutes to obtain water-containing Cu-MOG;

[0106] (4) The aqueous Cu-MOG obtained in step (3) was centrifugally washed three times with DMF and ultrapure water, and freeze-dried to obtain a dry Cu-MOG material.

[0107] Comparative Example 5

[0108] Degradation of DMNP by Cu-MOG

[0109] (1) The Cu-MOG material obtained in Comparative Example 4 was dispersed in ultrapure water to obtain a Cu-MOG material aqueous solution with a concentration of 0.82 mg / mL;

[0110] (2) taking 200 μL of DMNP ethanol solution (concentration of 2 mM) and adding it to a mixed solution containing 1000 μL of N-EM buffer solution, 300 μL of Cu-MOG material aqueous solution obtained in step (1) and 500 μL of H2O, mixing and reacting at room temperature for different time (1-150 min) to obtain reaction mixed solutions at different reaction times, and centrifuging all the above mixed solutions (12000 rpm, 1 min) to collect the supernatant;

[0111] (3) The absorbance of the supernatant in the range of 300-500 nm was measured by UV-visible spectrophotometer, where there was no obvious absorption peak at 402 nm. The results of the determination of the conversion rate of DMNP in the reaction system at different DMNP degradation times are shown in Fig.12 It can be seen that Cu-MOG material cannot degrade DMNP.

[0112] Comparative Example 6

[0113] (1) Dissolve Ti(SO4)2 (165.5 mg, 0.69 mmol) and Zn(NO3)2·6H2O (205.2 mg, 0.69 mmol) in 10 mL of ultrapure water respectively, and dissolve them completely by ultrasonication to obtain Ti(SO4)2 solution and Zn(NO3)2·6H2O solution with a concentration of 0.069 mol / L;

[0114] (2) 167.8 mg (0.69 mmol) of H3TATAB was added to 4 mL of ultrapure water, and 200 μL of TEA was added to promote its dissolution in water, followed by sonication to fully dissolve it. Finally, the solution was diluted to 5 mL to obtain a H3TATAB solution with a concentration of 0.138 mol / L;

[0115] (3) 333 μL of the Ti(SO4)2 solution obtained in step (1) was mixed with 21 μL of the Zn(NO3)2·6H2O solution and 146 μL of H2O to obtain a 500 μL mixed solution, and then 500 μL of the H3TATAB solution obtained in step (2) was quickly added to the mixed solution and vortexed for 2 seconds. After standing at room temperature for 15 minutes, water-containing TiZn-MOG was obtained;

[0116] (4) The aqueous TiZn-MOG obtained in step (3) was centrifugally washed three times with DMF and ultrapure water, and freeze-dried to obtain a dry TiZn-MOG material.

[0117] Comparative Example 7

[0118] Degradation of DMNP by TiZn-MOG

[0119] (1) The TiZn-MOG material obtained in Comparative Example 6 was dispersed in ultrapure water to obtain a TiZn-MOG material aqueous solution with a concentration of 0.82 mg / mL;

[0120] (2) taking 200 μL of DMNP ethanol solution (concentration of 2 mM) and adding it to a mixed solution containing 1000 μL of N-EM buffer solution, 300 μL of TiZn-MOG material aqueous solution obtained in step (1) and 500 μL of H2O, mixing and reacting at room temperature for different time (1-150 min) to obtain reaction mixed solutions at different reaction times, and centrifuging all the above mixed solutions (12000 rpm, 1 min) to collect the supernatant;

[0121] (3) The absorbance of the supernatant in the range of 300-500 nm was measured by UV-visible spectrophotometer, where there was no obvious absorption peak at 402 nm. The results of the determination of the conversion rate of DMNP in the reaction system at different DMNP degradation times are shown in Fig.13 It can be seen that TiZn-MOG material cannot degrade DMNP.

[0122] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a ZrCu-MOG material for cascade degradation of organophosphorus nerve agents, characterized in that: Zr 4+ and Cu 2+ The mixed solution is mixed with 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution at room temperature, allowed to stand, washed, and dried to obtain the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents; The concentration of the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 0.138 mol / L; The Zr-containing 4+ and Cu 2+ The volume ratio of the mixed solution to the 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine solution is 1:1; The Zr-containing 4+ and Cu 2+ The mixed solution consists of Zr with a concentration of 0.069 mol / L 4+ solution and Cu with a concentration of 0.069 mol / L 2+ The solution is prepared.

2. The method for preparing the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents according to claim 1, characterized in that: The Zr 4+ Solution and Cu 2+ The volume ratio of the solution is 333:

21.

3. A ZrCu-MOG material for cascade degradation of organophosphorus nerve agents prepared by the preparation method according to any one of claims 1-2.

4. The use of the ZrCu-MOG material for cascade degradation of organophosphorus nerve agents as claimed in claim 3 in cascade degradation of organophosphorus nerve agents, characterized in that: The organophosphorus nerve agent is methyl paraoxon, and the ZrCu-MOG material cascade degrades methyl paraoxon into p-aminophenol.

5. The use according to claim 4, characterized in that: The following steps are involved: The ZrCu-MOG material for cascade degradation of organophosphorus nerve agents is dissolved in water to obtain a ZrCu-MOG material aqueous solution, and mixed with a methyl paraoxon solution and an N-ethylmorpholine buffer solution at room temperature to degrade the methyl paraoxon into p-nitrophenol. Then, a NaBH4 solution is added to the mixed solution after the above reaction, and after mixing and reacting at room temperature, the p-nitrophenol is degraded into p-aminophenol, thereby realizing the cascade degradation of methyl paraoxon.

6. The use according to claim 5, characterized in that: The concentration of the ZrCu-MOG material aqueous solution is 0.82 mg / mL, and the concentration of the NaBH4 solution is 0.5M.

7. The use according to claim 5, characterized in that: The volume ratio of the ZrCu-MOG material aqueous solution to the methyl paraoxon solution and the NaBH4 solution is 3:2:4.

Citation Information

Patent Citations

  • Preparation method of organophosphorus degrading enzyme-based multifunctional catalyst, organophosphorus degrading enzyme-based multifunctional catalyst and application of organophosphorus degrading enzyme-based multifunctional catalyst

    CN111690637A

  • Method for constructing hybrid catalyst and cascade degradation of organophosphorus nerve poison by fixing palladium and organophosphorus hydrolase by using COFs

    CN112871211A

  • Micron-scale elemental copper catalyst and preparation method and application thereof

    CN104028268A

  • Method for rapidly preparing metal organic layer material and application

    CN111804346A